School Readiness of Supplemental Fed Preschoolers in Maguindanao - Dalgan, Norma; Camua, Amour; Camua, Amour; Abellar, Melda; Daglok, Sittie Rahema; Tabulong, Analie (Advances in Social Sciences Research Journal, 2021)
Please Pass the Bread” (PPtB) feeding program is an international program that aims to reduce the number of malnurished children in the province of Maguindanao. Thus, this study sought to determine the School Readiness of Supplementally Fed Preschoolers in Maguindanao. Specifically, the study determined the significant improvement of the preschoolers’ scores after the intervention (“Please Pass the Bread” (PPtB) feeding program). The pretest-posttest design of research was used, with the School Readiness Year-end Assessment Checklist (SReYA). The Checklist was the main tool for data gathering. The mean and percentage counts were used to describe the pretest and posttest score of the preschoolers. The t-test was used to determine the significant difference between the pupils’ pretest and posttest scores. The t-value was set at 0.05 levels of significance. Findings show that there is a significant difference in gain between the control and experiment group. This implies that the scores of the pupils improved significant after the exposure to the Please Pass the Bread” (PPtB) feeding program intervention. This mean that “Please Pass the Bread” (PPtB) feeding program intervention really helped improved the pupils’ school readiness. Thus, it is concluded that the “Please Pass the Bread” (PPtB) feeding program intervention significantly improves the readiness of the preschooler children in Maguindanao.